Hubungan Literasi Kesehatan dengan Kualitas Hidup Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Susoh Kabupaten Aceh Barat Daya - Rasima, Rasima; Munazar, Munazar; Lizam, T. CUT; Usrina, Nora; Yusnaini, Yusnaini; Yasni, Hilma; Sasmita, Yenni (Jurnal Ragam Pengabdian, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by insufficient insulin production or impaired insulin function, resulting in elevated blood glucose levels that can damage blood vessels, nerves, and other organs. This study aimed to examine the relationship between health literacy and the quality of life of patients with diabetes mellitus at the Susoh Community Health Center, Southwest Aceh Regency. An analytical observational study with a cross-sectional design was conducted involving 51 respondents selected through accidental sampling. Data were collected using structured questionnaires and analyzed using univariate, bivariate, and multivariate analyses with the Chi-square test. The results showed that 31% of respondents had poor quality of life, while 68% had good health literacy. Most respondents were older adults (90%), female (68%), had higher education (43%), were employed (68%), had higher income (56%), had a family history of DM (72%), adequate access to health information (66%), and low physical activity (52%). Bivariate analysis demonstrated significant associations between health literacy (p=0.016), family history of DM (p=0.029), and health information systems (p=0.010) with quality of life. Multivariate analysis identified the health information system as the strongest associated factor (p=0.014). Improving health literacy and access to health information may enhance the quality of life of patients with diabetes mellitus.